(untitled) (Revista Argentina de Musicología, 2012)
This paper deals with the treatment of soundscapes in music. Specifically the plan is to review the auditory perception of distance and its relation to the composition, both in instrumental and electroacoustic music. Firstly, a brief review of scientific evidence related —to involved in auditory— perception of distance. Secondly we review some strategies used by composers to simulate the location of sound sources in terms of distance, in real and virtual environments. Finally we develop concepts about sound production through multiple layers of emitting sound source as well as through the use of stationary sources of reference.